(untitled) (Research, Society and Development, 2022)
Introduction: Cardiorespiratory arrest in pregnant women is a rare event, however, it is essential that health professionals have adequate knowledge of how to perform the maneuvers if it happens, since the pregnant woman has some particularities that are different from other adults. Objective: To emphasize the importance of correctly performing cardiopulmonary resuscitation maneuvers in pregnant women Methodology: A search was carried out in the Virtual Health Library (BVS) in January 2022. health sciences (DeCS) Pregnancy; cardiorespiratory arrest; Cardiopulmonary resuscitation. The "and" baller was used and the following criteria were adopted for the selection of articles: complete materials, in Portuguese, in article format and with a time frame of ten years (2012-2022). Results: For the development of the study, readings and detailed analyzes of six documents found from the search carried out previously were carried out. Conclusion: This research emphasizes that cardiopulmonary resuscitation maneuvers in pregnant women have their particularities, and it is possible to observe the importance of this knowledge during the procedure so that it is successfully completed.